2013
DOI: 10.4236/acs.2013.33042
|View full text |Cite
|
Sign up to set email alerts
|

An Air Mass Based Approach to the Establishment of Spring Season Synoptic Characteristics in the Northeast United States

Abstract: The Northeast United States spring is indicative of major meteorological and biological change though the seasonal boundaries are difficult to define and may even be changing with global climate warming. This research aims to obtain a synoptic meteorological definition of the spring season through an assessment of air mass frequency over the past 60 years. The validity of recent speculations that the onset and termination of spring have changed in recent decades with global change is also examined. The Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…While studies have showed shifts in weather types (Zander et al , ), poleward shifts in jet stream patterns (Strong and Davis, ; Fu and Lin, ), and changes in surface seasonal characteristics (Dong et al , ; Ault et al , ), few have considered multiple layers of the atmosphere in a single study (e.g. Frauenfeld and Davis, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have showed shifts in weather types (Zander et al , ), poleward shifts in jet stream patterns (Strong and Davis, ; Fu and Lin, ), and changes in surface seasonal characteristics (Dong et al , ; Ault et al , ), few have considered multiple layers of the atmosphere in a single study (e.g. Frauenfeld and Davis, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study also found regional differences as northern China experienced more significant changes than the south. Zander et al () used the Spatial Synoptic Classification (Sheridan, ) to show an earlier arrival of springtime weather types (1950–2000) in the northeast United States. The authors also noted an increase in day‐to‐day variability near the end of the season.…”
Section: Introductionmentioning
confidence: 99%
“…They found later starts of autumn and winter and earlier onsets of spring and summer. It seems there is agreement on an earlier start date of spring in the works of Sparks and Menzel (2002) for Europe, Zander et al (2013) and Allen and Sheridan (2015) for the United States. Cassou and Cattiaux (2016) studied the effects a warmer world would have on seasons over Europe and found that winter onset would be slightly delayed and summer would start about 25 days earlier, which would be explained by the reduced March east-west temperature gradient linked to snow cover decline.…”
Section: Introductionmentioning
confidence: 89%
“…Reiser and Kutiel (2008) used a methodological approach to define the rainy season in the Mediterranean and its' characteristics (beginning/ending dates, length) and found that the region can be separated into two parts with a minimum in summer and a maximum in winter for the southern part, and a less pronounced annual course with a minimum in March and a maximum in June in the northern part. Zander et al (2013) attempted to synoptically define the spring season in the NE United States based on the type (moist/dry, polar/moderate/tropical) and frequency of air masses and also studied the spring temporal characteristics (start, end, duration) over the area. They found that the spring season is dry through time but recently has also been warmer and the start of the season is arriving earlier.…”
Section: Introductionmentioning
confidence: 99%
“…The consistent ranking of SWF as the largest exported of water and solutes during springtime points toward the synoptic-scale control of this export, whereby the magnitude of the solutes exported are dependent on wintertime conditions and accumulations (Elliott & Henry, 2009;Groffman et al, 2011;Judd et al, 2007), the general trend under SWF conditions is the same. Springtime SWF storms tend to be stronger in this season compared to others due to greater instability in the atmosphere from interacting air masses (Murray & Colle, 2011;Zander et al, 2013) leading to higher seasonal precipitation, discharge, and thus solute flux relative to other seasons.…”
Section: Seasonality Of Discharge and Solute Fluxesmentioning
confidence: 97%